(3GdQSGdI GdaJMjIs - (3eMjj GdOjf eMeO YHO GdMejO GddGPbj,J (B849 (3g` s ((3Ydi Hf Ndjd GdHUjQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CPGbfG MdGhI CdMGf YfGOd hQO LeGdg ai OhGFQ QhVGJ GdZHQGA HceGd bOQJg hQCaJI s
(3BNQgG (B:s
(3Cf cGf GdONhd Ydi GdfZeI ebOekG Sej Pdc (B((3HYO(B) (3hEf cGf HGdYcS Sei bHd s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B54 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHg GdCMeOjg HMdH (B(1206) s
Keywords: (3GdehSjbi hGdZfGAs